Effect of piles on the seismic response of mosques minarets - Mohamed Ahmed Abdel-Motaal (Ain Shams Engineering Journal, 2014)
Minarets seismic behavior is not similar to other known structures, because of their unique characteristics such as slenderness, shape, and supporting system. This study is devoted to investigate pile foundation effects on minarets dynamic response. An advanced finite element models were employed to simulate this sophisticated problem. The analysis procedure is essentially 2-D model enhanced to satisfy the requirements of 3-D problems, using transmitting and viscous boundaries. Root mean square procedure is implemented to minimize the needed computer memory. The model has a main advantage of considering the full interaction between soil, foundation, and structure. Three artificial earthquakes’ time histories were used as control motions at the bedrock surface. Minaret (60.0-m height) was studied to investigate the effects of soil stiffness, pile length, diameter, and arrangement, on the minaret and pile dynamic behavior. Comparison between study results and conventional analysis method is illustrated. Study results, discussion, and conclusion are given.